Lesson 4 - Musical Scales, Properties of Music and Musical Instruments / Lesson 4 - Musical Scales, Properties of Music and Musical Instruments - Πολίτης Διονύσιος (ΑΡΙΣΤΟΤΕΛΕΙΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΘΕΣΣΑΛΟΝΙΚΗΣ, 2016)
Lesson 4 - Musical Scales, Properties of Music and Musical Instruments